2020
DOI: 10.3390/ma13173679
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Activation Method of Rubber on the Performance of Modified Asphalt Binder

Abstract: Poor storage stability is a key problem restricting the rapid development and wide application of rubber-modified asphalt binder, and activation of rubber has shown good prospects to solve this problem. In this study, two activation methods, coating by polyamide 6 and grafting by acrylamide, were introduced to treat crumb rubber. Then the activated rubber was added to base asphalt binder to prepare modified asphalt binder. The chemical structure and morphology of rubber powder before and after activation and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Ortega et al [ 32 ] found that there was a chemical reaction between the anhydride group of dodecenyl succinic anhydride (DSA) and asphalt. By grafting the rubber with acrylamide and then modifying the asphalt, Xie et al [ 33 ] found that chemical interactions between the basic amide group of acrylamide and asphalt occurred. Therefore, the graft activation of SBS can cause the asphalt to react with the grafted part, which can increase the chemical effect between SBS and asphalt.…”
Section: Resultsmentioning
confidence: 99%
“…Ortega et al [ 32 ] found that there was a chemical reaction between the anhydride group of dodecenyl succinic anhydride (DSA) and asphalt. By grafting the rubber with acrylamide and then modifying the asphalt, Xie et al [ 33 ] found that chemical interactions between the basic amide group of acrylamide and asphalt occurred. Therefore, the graft activation of SBS can cause the asphalt to react with the grafted part, which can increase the chemical effect between SBS and asphalt.…”
Section: Resultsmentioning
confidence: 99%
“…The results from tests including viscosity at 175 • C, complex modulus, phase angle, and rutting factor indicate that activated crumb rubber enhances the modified bitumen's capacity to withstand dynamic loads and recover from deformation, thereby enhancing its high-temperature rheological properties. Other studies [121] investigated the use of two methods to activate CR, coating by polyamide and grafting by acrylamide. The results showed that both activation methods improved the high-and low-temperature performance of the bituminous binder by enhancing the interaction between the rubber and binder; however, grafting activation by acrylamide was found to be more effective due to the chemical reaction between groups of acrylamide and binder.…”
Section: Chemical Graftingmentioning
confidence: 99%
“…The group also evaluated the compatibility of asphalt binder with rubber surfaces activated by grafting polyamide 6 and showed its potential in improving the softening point, viscosity, and hightemperature and low-temperature properties of asphalt. 79 According to Hanet al, 80 the high compatibility between asphalt and rubber grafted with octadecyl amine can be due to chemical bonds formed between the amino group (−NH 2 ) on the octadecyl amine and the interfacial carboxyl group (−COOH) of waste rubber. Two additional examples of materials that have been used for rubber functionalization are polystyrene and acrylic acid.…”
Section: Thermomechanical Treatmentmentioning
confidence: 99%
“…%, the functionalized rubber outperformed regular crumb rubbers in improving the high- and low-temperature properties of asphalt. The group also evaluated the compatibility of asphalt binder with rubber surfaces activated by grafting polyamide 6 and showed its potential in improving the softening point, viscosity, and high-temperature and low-temperature properties of asphalt . According to Hanet al, the high compatibility between asphalt and rubber grafted with octadecyl amine can be due to chemical bonds formed between the amino group (−NH 2 ) on the octadecyl amine and the interfacial carboxyl group (−COOH) of waste rubber.…”
Section: Rubber Treatment Technologiesmentioning
confidence: 99%